(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Background: Cyclodestructive procedures with high laser energy settings achieve their IOP reduction effect at the expense of damage to the secretory epithelium of the ciliary processes and adjacent structures, which may result in such complications as hypotony and ocular subatrophy. Purpose: To experimentally evaluate the histopathological features in the rabbit eye after exposure of the distal ciliary body to transscleral selective laser radiation at the 810 nm wavelength versus the 1064 nm wavelength, and to compare the histopathological effects of the diode and neodymium:yttrium-aluminum-garnet (Nd:YAG) lasers. Material and Methods: Four Chinchilla rabbits (8 eyes) were included in this experimental study. In four eyes, transscleral cyclophotocoagulation (TSCPC) of the ciliary body was performed with an 1064-nm Nd:YAG laser (energy, 1.0 J/ pulse; pulse duration, 3 ms) equipped with a 600-µm fused-silica fiber optic tip. In another four eyes, an 810-nm diode laser TSCPC of the ciliary body was performed using a Vitra 810 apparatus (Quantel Medical Instruments, France) with a laser power of 1W and exposure duration of 1.5 s (energy, 1.5 J/pulse). Results: Our experimental histopathological study of rabbit eyes demonstrated no significant difference in the development of ciliary stromal edema (р = 0.425) and focal necrosis of the non-pigmented ciliary epithelium (р = 0.764) between the eyes that received the transscleral contact cyclodestruction with an 810-nm diode laser at an energy of 1.5 J and the eyes that received transscleral contact-and-compression cyclodestruction with a 1064-nm Nd:YAG laser at en energy of 1.0 J. Conclusion: The use of 810-nm laser radiation at energy of 1.5 J in the transscleral contact cyclodestruction and the use of 1064-nm laser radiation at energy of 1.0 J in the transscleral contact-and-compression cyclodestruction were similar in enabling selective thermal effects on the ciliary epithelium with limited damage to adjacent structures in rabbits.